2014
DOI: 10.1017/jfm.2014.548
|View full text |Cite
|
Sign up to set email alerts
|

Self-sustained oscillations of shallow flow past sequential cavities

Abstract: Shallow flow past successive cavities is characterized by means of high-image-density particle image velocimetry (PIV). Highly coherent, self-sustained oscillations arise due to coupling between the inherent instability of the separated shear layer along the opening of each sequential cavity; and a gravity standing wave mode within each cavity. The globally coupled nature of the flow structure is evident through dominance of the same spectral component in the undulating vorticity layers along each of the succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…The contours indicate that larger vortices are produced in the two side-wall cavities at the higher value of inlet velocity, as would be expected. The present results are in qualitative agreement with those of Tuna and Rockwell [14] (Fig.5), implying that the shallow flow solver gives a potentially useful representation of flowinduced vortices in adjacent side-wall cavities separated by a single groyne. The coupled shallow flow and particle-tracking model is then used to simulate advection and mixing processes in the side-wall cavities divided by the groyne, owing to the presence of the two recirculation zones, one in each cavity.…”
Section: Particle Advection In a Pair Of Adjacent Side-wall Cavitiessupporting
confidence: 89%
See 3 more Smart Citations
“…The contours indicate that larger vortices are produced in the two side-wall cavities at the higher value of inlet velocity, as would be expected. The present results are in qualitative agreement with those of Tuna and Rockwell [14] (Fig.5), implying that the shallow flow solver gives a potentially useful representation of flowinduced vortices in adjacent side-wall cavities separated by a single groyne. The coupled shallow flow and particle-tracking model is then used to simulate advection and mixing processes in the side-wall cavities divided by the groyne, owing to the presence of the two recirculation zones, one in each cavity.…”
Section: Particle Advection In a Pair Of Adjacent Side-wall Cavitiessupporting
confidence: 89%
“…As the stirrer strength µ increased from 0.05 to 1.5, the chaotic region grew until it filled much of the computational domain, in accordance with Aref's findings. The coupled shallow water flow and Lagrangian particle-tracking model was further validated against laboratory data for open channel flow past a pair of adjacent side-wall cavities obtained by Tuna and Rockwell [14] . Results were presented for the advection of different coloured tracer particles in the region of the side-wall cavities and it was found that the majority of particles remained trapped in the side-wall cavities, with a tendency for the particles to roll up into a single whorl that filled each cavity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for Helmholtz oscillator, several experiments [21][22][23][24][25] and numerical simulations [26][27][28][29][30] have been conducted to reveal the self-excited mechanism, frequency characteristics, and pressure fluctuation. The impact characteristics of the jets were quite different from those of continuous jets.…”
Section: Flow Configurationmentioning
confidence: 99%